Culturally Responsive Pedagogy : Working towards Decolonization, Indigeneity and Interculturalism - Pirbhai-Illich, Fatima; Pete, Shauneen; Martin, Fran (Springer International Publishing Imprint : Palgrave Macmillan, 2017)
' ... an important read for educators, administrators and policy makers ... a very welcome addition to studies of decolonial education and the poetics and politics of educational futurity.' -George J. Sefa Dei, Professor of Social Justice Education, University of Toronto, Canada ' ... an important read for those working and researching in anti-oppressive education ... challenges us to engage critically with the theory and practice of culturally responsive pedagogy as it aims to reform and reorient teacher education as a transgressive space.' -Jennifer Tupper, Dean, Faculty of Education, University of Regina, Canada.